Innate immune responses are increased in chronic obstructive pulmonary disease. - Katherine Joanne Baines (Public Library of Science (PLoS), 2011)
Background Chronic obstructive pulmonary disease (COPD) is characterised by irreversible airflow obstruction, neutrophilic airway inflammation and chronic bacterial colonisation, however the role of the innate immune response in the pathogenesis of COPD remains unclear. Methods Induced sputum was obtained from adults with COPD (n=22), and healthy controls (n=29) and was processed for differential cell counts. The sputum supernatant was assayed for innate immune mediators using ELISA, whilst sputum gene expression was measured using real-time PCR. Peripheral blood neutrophils were isolated and their response to lipopolysaccaride (LPS) stimulation was assessed in a subgroup of participants with COPD (n=13) and healthy controls (n=21). Results Participants with COPD had significantly higher protein levels of interleukin (IL)-8, and neutrophil elastase (NE) and detection of oncostatin M (OSM) compared to healthy controls. Gene expression for toll-like receptor (TLR) 2, IL-8 and OSM were also significantly higher in COPD participants. The level of IL-1β, surfactant protein (SP)-A, matrix metalloproteinase (MMP)-9 and TLR4 mRNA was not significantly different between groups. The level of innate immune response markers were highly associated with the presence of sputum neutrophils, each other and the degree of airflow limitation (FEV1/FVC). Peripheral blood neutrophils from participants with COPD had an increased response to stimulation by LPS; with a greater fold increase in the production of IL-8 and MMP-9 protein, and gene expression of IL-8, TLR2 and TLR4. Conclusions The innate immune response is increased in the airways and circulating neutrophils in COPD, and may be an important mechanism involved in disease pathogenesis.